Comparison of the Efficacy of ShuoTong Ureteroscopy and Simple Flexible Ureteroscopy in the Treatment of Unilateral Upper Ureteral Calculi - Lai, Longhui; Zhang, Wenzhao; Zheng, Fangjian; Wang, Tao; Bai, Peide; Liu, Zhengsheng; Zheng, Jiaxin; Shao, Zhiqiang; Duan, Bo; Wang, Huiqiang; Xing, Jinchun; Chen, Huixin; et al. (Frontiers in Surgery, 2021)
Background: ShuoTong Ureteroscopy (Sotn-ureteroscopy, ST-URS), a new lithotripsy operation method developed on the basis of ureteroscopy, is widely used to treat ureteral stones in China. Its composition includes: rigid ureteral access sheath, standard Mirror, lithotripsy mirror and ShuoTong perfusion aspirator. Here, we compared the efficacy and safety of ST-URS and flexible ureteroscope holmium laser lithotripsy in the treatment of unilateral upper ureteral calculi. Methods: Retrospective analysis was conducted on the clinical data of 280 patients who met the inclusion (① Urinary tract CT was diagnosed with unilateral single upper ureteral calculi above the L4 lumbar spine); ② Patient age was from 18 to 80 years old; ③Patients were informed and consented to this study; ④ Patients were approved with the hospital ethics committee (proof number: KY-2019-020).) and exclusion criteria for unilateral upper ureteral calculi in the First Affiliated Hospital of Xiamen University from January 2018 to November 2020, and they were divided into ST-URS group and the F-URS group. Results: The stone-free rate of 1 day after operation of ST-URS group was significantly higher than F-URS group (63.71% vs 34.62%, P < 0.0001). The operative time (38.45 min vs 46.18 min, P = 0.005) and hospitalization cost (27203 Yuan vs 33220 Yuan, P < 0.0001) of the ST-URS group were significantly lower than the F-URS group. There were no significant differences in the success rate of ureteral access sheath placement, operative blood loss, stone-free rate of 1 month after operation, postoperative complications, postoperative hospital stay and postoperative VAS pain score between the two groups (P > 0.05). In subgroups of diameter of calculi ≥ 1.5cm, calculi CT numerical value ≥ 1000HU and the preoperative hydronephrosis range ≥ 3.0 cm, ST-URS shows more advantages in the operative time, stone-free rate of 1 day after operation, the hospitalization cost and incidence of postoperative complications. Conclusions: In unilateral upper ureteral stones treated with a holmium laser, compared with the simple F-URS, the ST-URS has shorter operative time, lower hospitalization cost and higher stone-free rate of 1 day after operation, suggesting ST-URS could be more widely applied in clinics.